(3GdchGcH GdRgQjI aj GdNWH GdCRgQjIs - (3GdMGLQj, LGO Gdehdi, eMeO Hf eYOGf, J(B1229(3g`s ((3eMeO Hf YHO Gddg GdbdeGhjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CWdY TehS GdgOGjI aj bdhH Cgd GdYQaGf hCWeY fahS Cgd GdZhGjI aj hQhO efgd GdZaQGfs
(3BNQgG (B:s
{(3jG CjgG GdPjf BefhG EfeG GdNeQ hGdejSQ hGdCfUGH hGdCRdGe QLS ef Yed GdTjWGf aGLJfHhg dYdce JadMhf(B} (3HGQc Gddg dj hdce Edi GdBNQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 105s
(3eYLe GdeDdajf(B: 3 / 727s
(3EjVGM Gdecfhf(B: 2 / 391s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs